Retroperitoneal fibrosis is still underdiagnosed entity with poor prognosis - Izabela Łoń; Monika Wieliczko; Jacek Lewandowski; Jolanta Małyszko (Karger Publishers, 2021)
Background: Retroperitoneal fibrosis (RPF) is a rare disease characterized by the presence of inflammatory and fibrous retroperitoneal tissue that often encircles abdominal organs including aorta and ureters. Data on the incidence of this disease are limited. Summary: The disease may be idiopathic or secondary to infections, malignancies, drugs or radiotherapy. Idiopathic form is an immune-mediated entity and a part of the broader spectrum of idiopathic diseases termed chronic periaortitis, characterized by a morphologically similar fibroinflammatory changes in aorta and surrounding tissues. Taking into account the dominant symptoms and clinical charac-teristics of patients with periaortitis, two subtypes of disease could be distinguished. Vascular subtype include patients with non-dilated aorta or with inflammatory abdominal aortic aneu-rysm, both with and without involvement of adjacent structures and with numerous risk factors for atherosclerosis. In renoureteral subtype obstructive uropathy manifesting with hydronephro-sis and acute kidney injury is predominant finding. Due to the variety of symptoms, diagnosis of RPF remains challenging, difficult and often delayed. A series of diagnostic tests should be performed, in order to confirm the diagnosis idiopathic RPF. Laboratory work-up include eval-uation of inflammatory indices and immunological studies. A biopsy and histopathological evaluation may be necessary to confirm diagnosis and differentiate the disease. Computed to-mography (CT), magnetic resonance imaging (MRI) and positron emission tomography (PET) are the modalities of choice for the diagnosis and follow-up of this disease. Management of ureteral obstruction, hydronephrosis, and aortic aneurysms often requires surgical evaluation and treatment. The pharmacological treatment of RPF has been evaluated in a few randomized trials and is mainly based on observational studies. Steroid therapy remains the gold standard of treatment. Key messages: Nowadays multidisciplinary team approach with clinical and diagnos-tic experience in both primary and secondary RPF as well as two major subtypes should be offered. Centers specialized in rare diseases with collaboration with other units and referral sys-tem yield the best possible outcomes.